Parent artery stenting as a rescue management for stretched coils during cerebral aneurysms embolization: Report of three cases and review of literature. Issue 5 (October 2022) - Abdelrady, Mohamed M; Ognard, Julien; Abdelsamad, Amr M; Mahmoud, Mostafa
Background: Displacement of a stretched coil into the parent artery during intracranial aneurysm coiling is a challenging situation where the risk of acute intravascular thrombosis might be a life-threatening condition. The usual way of management is coil snaring, yet in some cases, it might not be feasible to retrieve the coil. Parent artery rescue stenting had already been described as a way of management in acutely thrombosed parent arteries during aneurysm coiling. Case reports: We present three cases with an inadvertent displacement of the unraveled coils into the parent artery for which rescue stenting was carried out to crush the coil against the vessel wall aiming to eliminate its thrombogenic effect. Our preliminary experience is that rescue stenting of the parent artery for stretched coil could be a convenient effective option particularly in case of failed/risky snaring with no notable immediate or long-term complications. Review and discussion: We review the reported cases of stretched coils with or without further unraveling and fracture and discuss the possible consequences, salvage methods, and clinical outcomes. Neurointerventionists should be aware of this complication and get acquainted with bailout strategies.